2D Magnetic profile data crossing the Mangatolu Triple Junction and the Fonualei Rift Spreading Centre in the northern Lau Basin, measured along profile P02 during SONNE cruise SO267 - Udo Barckhausen; Ingo Heyde; Heidrun Kopp (PANGAEA, 2022)
The dataset comprises measurements of the total intensity of the magnetic field measured with a towed Overhauser sensor and calculated magnetic anomalies. The data were measured along a E-W trending profile at ~16°S in the northern Lau Basin and were acquired in January 2019 as part of the SO267 cruise.